Elder self-neglect: research and practice - Dong XQ (Dove Medical Press, 2017)
XinQi Dong Rush Institute for Healthy Aging, Rush University Medical Center, Chicago, IL, USA Abstract: Elder self-neglect is a global public health and human rights issue that threatens older people’s health and safety. It commonly refers to refusal or failure to provide oneself with care and protection in areas of food, water, clothing, hygiene, medication, living environments, and safety precautions. While prevalent, the status of self-neglecting individuals remains largely unclear, in particular within community-dwelling populations. By reviewing the epidemiology of elder self-neglect (definition, prevalence, risk factors, and consequences) to date, the present paper identifies key research gaps such as methodological inconsistency in case identification and measurement, and study designs that are inadequate to determine risk factors of self-neglect. More importantly, in light of the rapidly growing older population, relevant stakeholders (researchers, healthcare providers, social service providers, legal professionals, community organizations, and policymakers) must be prepared for an expected increasing number of self-neglect cases and enlarging scope of the problem. Hence, in this article, I present an overview regarding the management issues of elderly self-neglect related to the detection, assessment, reporting and referral, and decision-making capacity. Based on the current literature, the paper is aimed to explore the present knowledge and challenges, and how they can pave the way for solutions to self-neglect research, practice, and policy. Keywords: elderly self-neglect, elder abuse, self-neglect future directions